First FDA Approved 3D Printed Drug Paved New Path for Increased Precision in Patient Care - Reddy, C. V.; V., Balamuralidhara; Venkatesh, M.P.; Pramod Kumar, T.M. (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2020)
The pharmaceutical industry is developed every year with the aim of public health, safety, and financial growth. Keeping public safety in mind, the industry is mostly concentrated on novel plans in the drug development process and plans on how to increase the curing rate of a disorder and building up the accuracy in patient care. The increase in the number of diseases has led to the generic and branded drug competition by which the pressure on the market has increased. The pharmaceutical manufacturers are attempting to find the needs of patients in different ways. The industries were manufacturing the drugs in unique ways which help to increase their productivity and also to increase the patient experience. Due to this, all pharmaceutical manufacturers are trying to manufacture drugs using 3D printing. In 2015, the industries succeeded by manufacturing the drug Spritam using 3D printing and it was the first prescribed drug manufactured by using 3D printing (3DP). 3DP is the process of depositing powder in a layer upon layer that was opposite to subtractive manufacturing and it is perfect for pharmaceuticals because it provides enhanced accuracy in the development and formulation of dosage forms. The 3DP has different advantages to companies and patients like an increase in dissolution rate, absorption, adherence, efficacy, and long life of branded drugs along with the decrease in pill burden. This process leads to a break in the manufacturing method of drugs but helps to overcome several problems and also helps in better patient outcomes in the solid dose markets.
Keywords: additive manufacturing